Unanswered questions and future direction in the management of terminal breathlessness in patients with cancer. (4th February 2020) - Mori, Masanori; Yamaguchi, Takashi; Matsuda, Yoshinobu; Suzuki, Kozue; Watanabe, Hiroaki; Matsunuma, Ryo; Kako, Jun; Imai, Kengo; Usui, Yuko; Matsumoto, Yoshihisa; Hui, David; Currow, David; et al.
Abstract : Breathlessness is among the most common and deteriorating symptoms in patients with advanced cancer, which may worsen towards the end of life. Breathlessness in patients with estimated life expectancy of weeks to days has unique clinical features: it tends to worsen rapidly over days to hours as death approaches often despite current symptom control measures. Breathlessness in patients during the last weeks to days of life can be called 'terminal breathlessness'. While evidence has accumulated for the management of breathlessness in patients with cancer who are not dying, such evidence may not be fully applied to terminal breathlessness. Only a few studies have investigated the best practice of terminal breathlessness in patients with cancer. In this paper, we summarise the current evidence for the management of terminal breathlessness, and propose future directions of clinical research.